Synthetic and Natural Insecticides: Gas, Liquid, Gel and Solid Formulations for Stored-Product and Food-Industry Pest Control - Stejskal, Vaclav; Vendl, Tomas; Aulicky, Radek; Athanassiou, Christos (Insects, 2021)
The selective application of insecticides is one of the cornerstones of integrated pest management (IPM) and management strategies for pest resistance to insecticides. The present work provides a comprehensive overview of the traditional and new methods for the application of gas, liquid, gel, and solid physical insecticide formulations to control stored-product and food industry urban pests from the taxa Acarina, Blattodea, Coleoptera, Diptera, Hymenoptera, Lepidoptera, Psocoptera, and Zygentoma. Various definitions and concepts historically and currently used for various pesticide application formulations and methods are also described. This review demonstrates that new technological advances have sparked renewed research interest in the optimization of conventional methods such as insecticide aerosols, sprays, fumigants, and inert gases. Insect growth regulators/disruptors (IGRs/IGDs) are increasingly employed in baits, aerosols, residual treatments, and as spray-residual protectants for long-term stored-grain protection. Insecticide-impregnated hypoxic multilayer bags have been proven to be one of the most promising low-cost and safe methods for hermetic grain storage in developing countries. Insecticide-impregnated netting and food baits were originally developed for the control of urban/medical pests and have been recognized as an innovative technology for the protection of stored commodities. New biodegradable acaricide gel coatings and nets have been suggested for the protection of ham meat. Tablets and satchels represent a new approach for the application of botanicals. Many emerging technologies can be found in the form of impregnated protective packaging (insect growth regulators/disruptors (IGRs/IGDs), natural repellents), pheromone-based attracticides, electrostatic dust or sprays, nanoparticles, edible artificial sweeteners, hydrogels, inert baits with synthetic attractants, biodegradable encapsulations of active ingredients, and cyanogenic protective grain coatings. Smart pest control technologies based on RNA-based gene silencing compounds incorporated into food baits stand at the forefront of current strategic research. Inert gases and dust (diatomaceous earth) are positive examples of alternatives to synthetic pesticide products, for which methods of application and their integration with other methods have been proposed and implemented in practice. Although many promising laboratory studies have been conducted on the biological activity of natural botanical insecticides, published studies demonstrating their effective industrial field usage in grain stores and food production facilities are scarce. This review shows that the current problems associated with the application of some natural botanical insecticides (e.g., sorption, stability, field efficacy, and smell) to some extent echo problems that were frequently encountered and addressed almost 100 years ago during the transition from ancient to modern classical chemical pest control methods.
Keywords: nanoparticles; essential oils; fumigation; impregnated nets; spray; diatomaceous earth; baits; insecticides; IPM; aerosol